use the distributive prperty to rewrite the expression without parentheses.

1. (-2a)(a+7)
2. (-3x)(-x^2+2)
3. (2x + 11)(5x)
4. (-2-3y)(-7y^2
5. (t-4)(-2)
6. (x)(x-5)

I'll do one for you to start you out.

1. (-2a)(a+7) = -2a^2-14a

Use a similar process to do the rest.

9(z+3)

To use the distributive property to rewrite an expression without parentheses, you need to multiply each term inside the parentheses by the term outside the parentheses. Here's how you can rewrite each expression:

1. (-2a)(a + 7) = -2a * a + (-2a) * 7 = -2a^2 - 14a

2. (-3x)(-x^2 + 2) = (-3x) * (-x^2) + (-3x) * 2 = 3x^3 - 6x

3. (2x + 11)(5x) = 2x * 5x + 11 * 5x = 10x^2 + 55x

4. (-2 - 3y)(-7y^2) = (-2) * (-7y^2) + (-3y) * (-7y^2) = 14y^2 - 21y^3

5. (t - 4)(-2) = t * (-2) + (-4) * (-2) = -2t + 8

6. (x)(x - 5) = x * x + x * (-5) = x^2 - 5x

By using the distributive property, you can rewrite expressions without parentheses and simplify them further if needed.